Click strategy using disodium salts of amino acids improves the water solubility of plinabulin and KPU-300. Issue 14 (15th July 2017) - Yakushiji, Fumika; Muguruma, Kyohei; Hayashi, Yoshiki; Shirasaka, Takuya; Kawamata, Ryosuke; Tanaka, Hironari; Yoshiwaka, Yushi; Taguchi, Akihiro; Takayama, Kentaro; Hayashi, Yoshio
Graphical abstract: Abstract: Plinabulin and KPU-300 are promising anti-microtubule agents; however, the low water solubility of these compounds (<0.1 µg/mL) has limited their pharmaceutical advantages. Here, we developed five water-soluble derivatives of plinabulin and KPU-300 with a click strategy using disodium salts of amino acids. The mother skeleton, diketopiperazine (DKP), was transformed into a monolactim-type alkyne and a copper-catalyzed alkyne azide cycloaddition (CuAAC) combined azides that was derived from amino acids as a water-solubilizing moiety. The conversion of carboxyl groups into disodium salts greatly improved the water solubility by 0.8 million times compared to the solubility of the parent molecules. In addition, the α-amino acid side chains of the water-solubilizing moieties affected both the water solubility and the half-lives of the compounds during enzymatic hydrolysis. Our effort to develop a variety of water-soluble derivatives using the click strategy has revealed that the replaceable water-solubilizing moieties can alter molecular solubility and stability under enzymatic hydrolysis. With this flexibility, we are approaching to the in vivo study using water-soluble derivative.